Externalities and inefficiencies caused by inadequate international coordination against the financial and economic crisis (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
The main objective of this paper is to analyze the inefficiencies that have led the several measures taken by governments to prevent financial systems bankruptcy and mitigate the effects of the financial crisis on the real economy. We review from acritical view of the limited international coordination the different support schemes applied for the financial sector and stimulate the economy in the United States andthe European Union.
Keywords: economic and financial crisis; spillovers; inefficiencies; support schemes for the financial sector; economic policy